Milk and dairy products consumption pattern and preferences in the Kilinochchi district of Sri Lanka - Kathirkamanathan, T.; Sinniah, J. (Eastern University Sri Lanka, 2023)
Current study was carried out in four divisional secretariats of Kilinochchi district to study the consumption pattern and preferences for milk and dairy products. Out of 45,016 households 1000 households were selected using table of random numbers. Information on consumption pattern and preferences for milk and dairy products by the consumers were collected using structured questionnaires. Data were processed using Microsoft Excel 2007 and analyzed using Proc frequency and Chi-square test. Overall around 38% of the households relied on their own source of milk for consumption; in the Kandavali and Poonagary divisional secretariats around 50% of the households relied on their own source of milk. Source of milk from cattle, goat and both averaged to around 76%, 8% and 16%, respectively. Overall consumption pattern of major milk and dairy products viz. was milk powder (26%), yoghurt (19%), fresh milk (15%), curd (14%), flavored milk (11%) and ghee (6%). Consumption level of other dairy products such as cheese, butter and milk toffee averaged to around 3%. Overall reasons for not taking milk for family consumption was do not like to drink milk (73%), insufficient income (20%) and fear of contamination (7%). Chi square test revealed significant association between milk and dairy products and preference order. Most of the households gave first preference for fresh milk (73%) and milk powder (68%) on a nine scale preference order. Most of the households showed a preference order of 2 nd (52%) and 3rd (37%) for curd. Significant percentage of households showed preferences for yoghurt, pasteurized milk, cheese, butter, ghee and milk toffee. Fresh milk consumption percentage of 15% is not an appreciable figure; hence, measures should be taken to encourage households to take milk for family consumption as well. Consumption pattern trend of various dairy products will pave way for value addition to milk and generate employment opportunities in the dairy value chain in the study area.
Keywords: Consumption pattern; Dairy product; Fresh milk; Kilinochchi preferences